Field Application Case Studies and Long-Term Monitoring of Bridges Utilizing the Simple for Dead–Continuous for Live Bridge System - Aaron Yakel; Atorod Azizinamini (Engineering Journal, 2014)
The performance of three bridges constructed using the simple for dead load and continuous for live load (SDCL) bridge system for steel girders was monitored during and after construction to compare actual performance with predicted performance. The structure types were a box-girder bridge, an I-girder bridge and a box-girder bridge built using accelerated construction details. During construction, strains and deflections were monitored so that the degree of continuity over the pier could be determined. The design concept assumes that a simply supported condition exists during casting of the concrete deck. However, to provide lateral bracing, the concrete diaphragm—or turndown—over the pier is cast and cured prior to casting the deck. As expected, encasement of the girders provides some continuity over the pier during casting of the deck. The degree of continuity over the pier can be reduced by lowering the height of the construction joint and through the use of crack-inducing details. Long-term monitoring of the structures showed the behavior to be consistent over time with no significant deviations from the predicted bridge behavior. During the initial time period of approximately 18 months, a slight overall change in strain values was observed in concrete elements. The rate of change slowed during this period and eventually ceased. Subsequently, the response of the structure has been consistent with only small seasonal fluctuations observed. These fluctuations are expected and are generally attributable to changes in ambient temperature, relative humidity, incident solar radiation and ground freeze/thaw conditions.